Implementation of the CORE Model with the Interventionist Assessment to Improve Students’ Mathematics Creative Thinking Ability - Sri Solihah; Kartono Kartono; S. Mariani️; Dwijanto Dwijanto (Universitas Negeri Semarang, 2022)
Low students' mathematical creative thinking ability. so that an innovative learning model is needed related to assessment before, during and after learning. This study aims to determine the effectiveness of the CORE Model with Interventionists Dynamic Assessment to Improve Students' Mathematical Creative Thinking Ability. This type of research is quantitative research. The population in this study were students of class XI in one of the high schools in the Ciamis district, teaching 2021/2022. The research sample with random sampling. The learning using the CORE model with interventionist dynamic assessment is very effective The results showed that (1) the average mathematical creative thinking ability of students who taught using the CORE model with Interventionist Dynamic Assessment more than the average mathematical creative thinking ability of students who taught using ordinary learning models, (2) mathematical creative thinking skills using the CORE model with Interventionist Dynamic Assessment achieve completeness of at least 65, (3) students' self-confidence affects the ability to think creatively by 35% .